Diplonemids - A Review on "New" Flagellates on the Oceanic Block - Tashyreva, Daria; Simpson, Alastair G B; Prokopchuk, Galina; Škodová-Sveráková, Ingrid; Butenko, Anzhelika; Hammond, Michael; George, Emma E; Flegontova, Olga; Záhonová, Kristína; Faktorová, Drahomíra; Yabuki, Akinori; Horák, Aleš; et al. (Protist, 2022)
Diplonemids are a group of flagellate protists, that belong to the phylum Euglenozoa alongside euglenids, symbiontids and kinetoplastids. They primarily inhabit marine environments, though are also found in freshwater lakes. Diplonemids have been considered as rare and unimportant eukaryotes for over a century, with only a handful of species described until recently. However, thanks to their unprecedented diversity and abundance in the world oceans, diplonemids now attract increased attention. Recent improvements in isolation and cultivation have enabled characterization of several new genera, warranting a re-examination of all available knowledge gathered so far. Here we summarize available data on diplonemids, focusing on the recent advances in the fields of diversity, ecology, genomics, metabolism, and endosymbionts. We illustrate the life stages of cultivated genera, and summarise all reported interspecies associations, which in turn suggest lifestyles of predation and parasitism. This review also includes the latest classification of diplonemids, with a taxonomic revision of the genus Diplonema. Ongoing efforts to sequence various diplonemids suggest the presence of large and complex genomes, which correlate with the metabolic versatility observed in the model species Paradiplonema papillatum. Finally, we highlight its successful transformation into one of few genetically tractable marine protists.
Keywords: oceány a moře; ultrastructure; paraziti; Eukaryota; Parasites; zvířata; Oceans and Seas; Phylogeny; Animals; Protists; marine flagellates; ecology; Euglenozoa; taxonomic revision; fylogeneze